Productivity of thinned black locust (Robinia pseudoacacia L.) stands in Hungary: case studies - Rédei, Károly; Ábri, Tamás (Acta Agraria Debreceniensis, 2022)
Black locust (Robinia pseudoacacia L.) is one of the most important introduced tree species in Hungary, covering more than 24% of the stocked area and providing approximately 20% of the country’s annual timber cut. Consequently, the research and development activities related to the improvement of the growing technology of black locust are also important, especially in mitigating the negative effects of climate change. The aim of this study was to quantify growth and yield, responses of even-aged 12–31–year–old black locust stand to thinning in Hungary. The study has proved that irrespective of the yield class, age and thinning intensity, thinning could not increase effectively the cumulative volume production. As percentage of the control it has changed between +0.6 and -8.4%. On the other hand, it could increase the stand value based on stem quality index by 10–21%.